Art as Advocacy: The Intersection of Visual Culture and Human Rights in Indonesia (Indonesian Art and Justice Review, 2024)
In Indonesia, visual art has become an essential tool for advocating human rights, with artists using their work to address issues such as political oppression, social inequality, and environmental justice. This paper examines the intersection of art and human rights in Indonesia, analyzing how visual culture—through painting, photography, murals, and multimedia—has raised awareness about human rights abuses and sparked social and political change. The paper highlights key artists and art movements that have contributed to the human rights discourse in Indonesia, discussing the potential and limitations of art as a form of activism, and the ways in which art can influence public policy, community mobilization, and international attention.